Adapt : why success always starts with failure - Harford, Tim, 1973- (New York : Farrar, Straus and Giroux, 2011)
Outlines a counterintuitive approach to changing the world by assessing its failures, drawing on myriad disciplines to argue that complex challenges must be met through adaptive trial-and-error practices that do not depend on expert opinions or ready-made solutions.
Adapting -- Conflict or : How organizations learn -- Creating new ideas that matter or : Variation -- Finding what works for the poor or : Selection -- Climate change or : Changing the rules for success -- Preventing financial meltdowns or : Decoupling -- The adaptive organization -- Adapting and you.
Includes bibliographical references and index.
Keywords: Success; Adaptability (Psychology); Organizational change; Failure (Psychology); Adaptability (Psychology); Failure (Psychology); Organizational change; Success; Unternehmenserfolg; Anpassung; Misserfolg; Unternehmenserfolg; Misserfolg; Unternehmen; Erfolg; Erfolgsfaktor; Misserfolg; Adjustment (Psychology); Success; Unternehmenserfolg; Lernende Organisation